(untitled) (The Journal of Medicine, Humanity and Media, 2025)
This article reviews the inaugural lecture of the MHM2025 special series delivered by Professor Shaohai Jiang, titled “Mixed Methods in Health Communication Research”. This lecture systematically explains the application value and practical path of mixed research methods in the field of health communication. Professor Shaohai Jiang demonstrated the synergy between quantitative and qualitative methods through interpretive and exploratory design; he used the Queenstown project as an example to illustrate the closed-loop application of formative research, process evaluation and summative evaluation in health communication activities; and he guided the students to apply social cognitive theories and other methodologies to the design of issues such as short-video addiction interventions and optimization of the healthcare experience in the classroom, so as to strengthen the problem-oriented research mindset.